Taxonomy, conservation, geographic and potential distribution of Macrotorus Perkins (Mollinedioideae, Monimiaceae), and a key to the Neotropical genera of Monimiaceae - de Lirio, Elton John; Peixoto, Ariane Luna; de Siqueira, Marinez Ferreira (Phytotaxa, 2015)
Macrotorus is a dioecious, monotypic genus that is endemic to the Brazilian Atlantic rainforest, where it occurs in lowland, submontane and montane forests; different from most other Monimiaceae in Atlantic rainforest, which are restricted to dense, humid, montane forests. Here, an updated description of Macrotorus utriculatus is provided, including the first description of the pistillate flowers, together with the lectotypification of the species, comparison with related genera, its conservation status, geographic distribution, and modeling of potential distribution. We also provide an identification key to the Neotropical genera of Monimiaceae.